2020
DOI: 10.3171/2019.6.jns191531
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 5-aminolevulinic acid and sodium fluorescein for intraoperative tumor visualization in patients with high-grade gliomas: a single-center retrospective study

Abstract: OBJECTIVEMaximal safe resection is an important surgical goal in the treatment for high-grade gliomas. Fluorescent dyes help the surgeon to distinguish malignant tissue from healthy. The aims of this study were 1) to compare the 2 fluorescent dyes 5-aminolevulinic acid (5-ALA) and sodium fluorescein (fluorescein) regarding extent of resection, progression-free survival, and overall survival; and 2) to assess the influence of other risk factors on clinical outcome and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Aside from 5-ALA other fluorophores were additionally investigated for fluorescence guided resection in HGG as well as LGG. One alternative to 5-ALA for intraoperative fluorescence represents sodium fluorescein (134)(135)(136)(137). Sodium fluorescein is a technique for intraoperative fluorescence-guided resection in HGG, however, it showed no benefit in LGG surgery as no intraoperative yellow fluorescence was evident in LGG tissue (138,139).…”
Section: Value Of Other Fluorophores In Lggmentioning
confidence: 99%
“…Aside from 5-ALA other fluorophores were additionally investigated for fluorescence guided resection in HGG as well as LGG. One alternative to 5-ALA for intraoperative fluorescence represents sodium fluorescein (134)(135)(136)(137). Sodium fluorescein is a technique for intraoperative fluorescence-guided resection in HGG, however, it showed no benefit in LGG surgery as no intraoperative yellow fluorescence was evident in LGG tissue (138,139).…”
Section: Value Of Other Fluorophores In Lggmentioning
confidence: 99%
“…Fluorescein sodium was used during surgery to improve the rate of gross total resection and visualize the tumor [ 38 , 40 ] ( Figure 2(a) ). Next, six pieces of CWs were placed into the suspected residual tumor cavity and fixed with bioabsorbable hemostatic meshes and fibrin sealant (Figures 2(b) – 2(f) ).…”
Section: Resultsmentioning
confidence: 99%
“…In patients undergoing reoperation of their recurrent GBM, Nabavi et al demonstrated that 5-ALA remains a useful tool in detecting recurrent gliomas, even after previous treatments with radiation, chemotherapy, or prior resections [13]. Recently, uorescein sodium has been shown to be a viable alternative to 5-ALA in uorescence-guided resection of malignant gliomas for both primary [14] and recurrent gliomas [15].…”
Section: Discussionmentioning
confidence: 99%